A striking new treehopper genus Mutilifolia (Hemiptera: Membracidae: Smiliinae: Telamonini), from Costa Rica - Wallace, Matthew S. (Zootaxa, 2015)
A new treehopper genus from Costa Rica, Mutilifolia, based on M. nishidai, new species, is described and illustrated. Mutilifolia is considered a member of the subfamily Smiliinae, tribe Telamonini based on characteristics of the pronotum, fore- and hind wing venation, and female genitalia. This genus superficially resembles the telamonine genera Antianthe, Archasia, and Hemicardiacus due to the highly elevated, foliaceous, and largely green pronotum, but the male style clasp of Mutilifolia with two recurved teeth differs greatly from the styles of any other presently known telamonine. Further collecting of treehoppers in the mountainous regions of Central America and Mexico, areas often neglected by collectors, may yield additional new Telamonini taxa.